2017
DOI: 10.3897/zookeys.651.10097
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the genus Laparocerus, with comments on colonisation and diversification in Macaronesia (Coleoptera, Curculionidae, Entiminae)

Abstract: The flightless Entiminae weevil genus Laparocerus is the species-richest genus, with 237 species and subspecies, inhabiting Macaronesia (Madeira archipelago, Selvagens, Canary Islands) and the continental ‘Macaronesian enclave’ in Morocco (one single polytypic species). This is the second contribution to gain insight of the genus and assist in its systematic revision with a mitochondrial phylogenetic analysis. It centres on the Canarian clade, adding the 12S rRNA gene to the combined set of COII and 16S rRNA u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 122 publications
(163 reference statements)
2
37
0
Order By: Relevance
“…These rates were also applied successfully by Xavier et al () and Panova, Nygren, Jonsson, and Leidenberger () in other two isopod genera ( Stenosoma and Idotea, respectively) and fit within the range of COI rates estimated for other marine arthropods (Knowlton & Weigt, ; Markow & Pfeiler, ; Sponer & Lessios ; Wares & Cunningham, ). The second and third priors were based on the hypotheses that D. edwardsi colonized La Palma (formed at around 1.7 Myr; Fernández‐Palacios et al, ; Guillou, Carracedo, & Duncan, ) and El Hierro (1.1 Myr; Carracedo, ; Fernández‐Palacios et al, ) shortly after the formation of the islands, as used by Machado, Rodríguez‐Expósito, López, and Hernández (). The corresponding clades were set to priors of 1.7 Myr (standard error of 0.17 Myr) and 1.1 Myr (standard error of 0.11 Myr).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These rates were also applied successfully by Xavier et al () and Panova, Nygren, Jonsson, and Leidenberger () in other two isopod genera ( Stenosoma and Idotea, respectively) and fit within the range of COI rates estimated for other marine arthropods (Knowlton & Weigt, ; Markow & Pfeiler, ; Sponer & Lessios ; Wares & Cunningham, ). The second and third priors were based on the hypotheses that D. edwardsi colonized La Palma (formed at around 1.7 Myr; Fernández‐Palacios et al, ; Guillou, Carracedo, & Duncan, ) and El Hierro (1.1 Myr; Carracedo, ; Fernández‐Palacios et al, ) shortly after the formation of the islands, as used by Machado, Rodríguez‐Expósito, López, and Hernández (). The corresponding clades were set to priors of 1.7 Myr (standard error of 0.17 Myr) and 1.1 Myr (standard error of 0.11 Myr).…”
Section: Methodsmentioning
confidence: 99%
“…Myr;Fernández-Palacios et al, 2011;Guillou, Carracedo, & Duncan, 2001) and El Hierro (1.1 Myr;Carracedo, 2011;Fernández- Palacios et al, 2011) shortly after the formation of the islands, as used byMachado, Rodríguez-Expósito, López, and Hernández (2017). Thecorresponding clades were set to priors of 1.7 Myr (standard error of 0.17 Myr) and 1.1 Myr (standard error of 0.11 Myr).…”
mentioning
confidence: 99%
“…Recent studies on a few flightless weevils have suggested that they have been able to colonize numerous remote archipelagos and islands likely due to their long and complex histories in the regions (Claridge et al, 2017;Machado et al, 2017;T€ anzler et al, 2016). However, the mechanism and transporting vectors of effective long-distance dispersal across oceanic barriers remain elusive for these weevils.…”
Section: Probable Mechanisms Of Overwater Dispersal Of Remote Oceanmentioning
confidence: 99%
“…The P. orbifer complex represents an excellent set of organisms to test the stepping-stone hypothesis, not only because of the existence of closely related endemic species on nearly every sizable island across the archipelago, but also due to three intriguing adaptations that may facilitate their cross-ocean dispersal through rafting on floating vegetation by oceanic currents: (1) Pachyrhynchus adults are wingless and have completely fused elytra; (2) they have the ability to draw and keep air under their elytra, allowing them to float on water for at least several hours (Schultze, 1923); (3) their eggs are inserted into plant tissues, and the larvae live and feed inside the stems of the host plants. Recent studies suggested that flightless weevils were able to colonize remote archipelagos of Southeast Asia and the Pacific via stepping-stone islands (Claridge, Gillespie, Brewer, & Roderick, 2017;Machado, Rodr ıguez-Exp osito, L opez, & Hern andez, 2017;T€ anzler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The comparative analysis of such independent events and the subsequent island radiation (both within and between islands) in different archipelagos provides new insights into the general evolutionary process generating biological diversity (Gillespie & Roderick, 2002;Losos & Ricklefs, 2009). Such approximation has been successfully applied in a number of studies on oceanic islands (Losos, Jackman, Larson, Queiroz, & Rodriguez-Schettino, 1998;Stroud & Losos, 2016), such as Hawaii (Gillespie, 2004), the Galapagos (Grant & Grant, 2008) and the Canary Islands and Madeira archipelagos (Juan, Emerson, Oromı, & Hewitt, 2000;Machado, Rodríguez-Expósito, López, & Hernández, 2017), where explicit hypotheses on the evolutionary processes underlying radiations have been tested.…”
mentioning
confidence: 99%